A Study on the Influence of Patient Participation on Patient Trust-Based on Sample Survey in China - Yang, Tongwei; Wu, Yijin (Frontiers in Psychology, 2018)
Trust plays a central role in a doctor – patient relationship, and patient’s trust in doctors is the most important factor in trust relationship between the doctor and the patient. By reviewing the existing studies, this study proposes that patient participation is an antecedent variable influencing patient trust, and the patient can take the initiative to participate in diagnostic activities with the aim of establishing and maintaining the psychological contract with the doctor, thereby strengthening doctor-patient trust. In this study, we propose the model on the relationship between the patient participation, the patient’s psychological contract and the patient trust, and then conduct an empirical study. The research findings indicate that patient participation is an antecedent variable for the patient’s psychological contract and patient trust; the patient’s psychological contract is a mediator variable between the patient participation and the patient’s trust in doctor; patient participation can be categorized as three dimensions: information search, responsible behavior, and interpersonal relationship. Thus, we should encourage patient participation, advocate the shared decision-making, and promote the synergic improvement of interpersonal trust and universal trust between doctors and patients.